Gut Microbiota Profiles and Microbial-Based Therapies in Post-operative Crohn's Disease: A Systematic Review - Zhuang, Xiaojun; Tian, Zhenyi; Li, Na; Mao, Ren; Li, Xiaozhi; Zhao, Min; Xiong, Shanshan; Zeng, Zhirong; Feng, Rui; Chen, Minhu (Frontiers in Medicine, 2021)
Background and Aims: Gut microbiota recolonization after intestinal resection had been reported to be associated with postoperative recurrence in Crohn’s disease (CD). However, the results of different studies are inconsistent and even contradictory. In addition, knowledge on the efficacy of microbial-targeted therapies in preventing postoperative recurrence of CD is limited. Therefore, the aim of this review was to investigate gut microbiota profiles in patients with CD before and after surgery, and evaluate microbial-targeted therapies in preventing postoperative recurrence. Methods: Electronic databases were searched from inception to 31 June 2020 using pre-defined terms. Studies that investigated gut microbiota pre- and post- intestinal resection, and microbial-targeted therapies in preventing postoperative recurrence, were eligible. Study quality was assessed using either the Newcastle-Ottawa scale or Jadad scoring system. Results: Twelve studies investigating gut microbiota of CD patients suffering from operation, and other 12 studies evaluating the efficacy of antibiotics and probiotics, were included in our review. The mucosa-associated microbiota in surgical biopsy of CD patients is significantly distinct from that in normal mucosa from healthy subjects. Gut microbiota recolonization following surgery might be associated with postoperative recurrence in CD patients. Furthermore, CD patients with postoperative recurrence presented a gain in pro-inflammatory pathogenic bacteria and a loss in short chain fatty acid-producing bacteria before and after surgery. However, no consistent bacteria or metabolites was found to predict the postoperative recurrence of CD. Additionally, microbial-targeted therapies are deficient, and present restricted widespread clinical utility due to several deficiencies. Conclusion: Recurrence-associated bacteria observed pre and post operation might be promising in preventing the postoperative recurrence of CD. Furthermore, potential microbe biomarkers for predicting subsequent disease recurrence should be validated with larger sample sizes using more rigorous and standardized methodologies.